Computer aided instruction for DC machine (using visual basic) / Suzana Mohd Zohdi - Mohd Zohdi, Suzana
This thesis presents a computer aided instruction (CAI) project, which assist undergraduate engineering students in learning dc machine. The project was developed using Visual Basic (VB) programming, an object-oriented programming language. The developed CAI software provides interactive teaching notes, animated graphics, attractive diagram and quiz to improve the effectiveness and understanding during the learning process. The overall purpose of this project is to improve the teaching and learning process through an individualized, guided and interactive environment, which corresponds to the diversity of student knowledge.